Corporate Environmental Sustainability Via Stakeholder Collaboration: Insights from Classical Institutional Economics - Valentinov, Vladislav (Journal of business ethics, 2026)
Stakeholder scholarship has made significant progress in identifying the factors that contribute to the successful impact of stakeholder collaborations on corporate environmental sustainability. An issue that has received less attention in this scholarship is an analysis of cases where stakeholder collaborations fail or encounter difficulties. To address this issue, we combine stakeholder theory with the unconventional perspective of classical institutional economics, which offers a critical view of corporate behavior. On this basis, we develop a conceptual framework that distinguishes four types of corporate behavior, ranging from disinterest in environmental protection to effective environmental behavior through managing for stakeholders. This framework allows us to formulate four propositions extending the extant stakeholder-theoretic analysis of corporate environmental sustainability. Our argument accommodates both successful and not so successful cases of stakeholder collaboration, strengthens the institutional economics foundation of stakeholder theory, and provides practical implications for corporate managers and policymakers.